A gC 3 N 4 / Ti 3 C 2 / Sn-Bi-MOF composite photocatalyst and its preparation method and application
By introducing Ti3C2 between the heterojunctions of g-C3N4 and Sn-Bi-MOF, a Z-type heterojunction and a Schottky junction are formed, the problems of slow electron transfer rate and high electron-hole recombination rate of the photocatalyst are solved, and the efficient photocatalytic reduction of CO2 is achieved.
Patent Information
- Application Number
- CN202311468966.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-11-07
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2043-11-07
AI Technical Summary
In the process of photocatalytic carbon dioxide reduction, existing photocatalytic electron transfer rate and high electron-hole recombination rate have problems, which limits their application efficiency.
By introducing Ti3C2 between the heterojunctions of g-C3N4 and Sn-Bi-MOF, a Z-type heterojunction and a Schottky junction are formed, thereby improving the transmission efficiency of electrons and suppressing electron-hole recombination.
The light absorption capacity and electron transfer rate of the photocatalyst are significantly improved, the CO2 reduction efficiency is improved, and the cycle stability is good.
Smart Images

Figure HDA0004534441530000011 
Figure HDA0004534441530000012 
Figure HDA0004534441530000021
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of photocatalytic reduction of carbon dioxide, and specifically relates to a Z-type heterojunction g-C3N4 / Ti3C2 / Sn-Bi-MOF composite photocatalyst and a preparation method and application thereof. Background Art
[0002] With the excessive use of fossil fuels in industrial development, too much carbon dioxide is emitted into the atmosphere, leading to the greenhouse effect. Therefore, the treatment of carbon dioxide in the atmosphere is imminent. At present, photocatalysis, electrocatalysis, thermal catalysis and many other methods are used to convert CO2. The main products of carbon dioxide reduction are renewable hydrocarbon fuels such as formic acid (HCOOH), formaldehyde (HCHO), methanol (CH3OH), methane (CH4) and important industrial raw materials such as carbon monoxide (CO) and two-carbon compounds (C2). Photocatalytic reduction of carbon dioxide to carbon monoxide and methane is considered to be one of the most effective reduction pathways.
[0003] Since the first report in 1979, many types of semiconductors have been explored, developed and improved for the photocatalytic reduction of CO2 using semiconductors, such as inorganic semiconductors, metal-doped zeolites, metal complexes, metal-organic frameworks (MOFs), and covalent organic frameworks (COFs). Among them, graphitic carbon nitride (g-C3N4) is the most attractive due to its excellent environment, appropriate conduction band edge, high chemical stability and efficient visible light absorption. However, there are also some disadvantages that hinder its development. The band gap of pure pCN is ~2.7eV, VB is 1.39eV, and CB is -1.24eV, resulting in a relatively short light absorption edge. In addition, the original g-C3N4 has low conductivity and high electron-hole recombination rate. Constructing heterojunctions and Schottky junctions is one of the effective measures to inhibit charge separation and electron transport in g-C3N4. Ti3C2 is widely used in the field of photocatalysis due to its ultra-high conductivity. It is usually used as a co-catalyst to form a Schottky junction with the material to improve the transmission of electrons and improve the photocatalytic effect.
[0004] In recent years, a functional inorganic organic catalyst with high specific surface area, high stability, large porosity and controllability, called metal organic frameworks (MOFs), has emerged, which is very attractive in the photocatalytic reduction of carbon dioxide. Among them, bimetallic MOFs not only have the porous structure of MOFs, but also have the ability to combine multiple reaction sites, providing a new idea for the photocatalytic reduction of carbon dioxide. In addition, the formation of heterojunctions can improve the electron-hole separation efficiency, thereby promoting the generation of active substances. However, due to its slow electron transfer rate, the generated electrons recombine with holes before being transferred, which limits its application in photocatalysis. Summary of the invention
[0005] In view of the shortcomings in the prior art, the present invention provides a g-C3N4 / Ti3C2 / Sn-Bi-MOF composite photocatalyst in which Ti3C2 is introduced between the heterojunction of g-C3N4 and Sn-Bi-MOF to form a Schottky junction, and a preparation method and application thereof. In the present invention, g-C3N4 and Sn-Bi-MOF are first prepared by calcination and hydrothermal methods respectively, Ti3C2 is then etched out by LiF, and then Ti3C2 and Sn-Bi-MOF are grown on the surface of g-C3N4 by mechanical stirring to prepare a g-C3N4 / Ti3C2 / Sn-Bi-MOF composite photocatalyst; the g-C3N4 / Ti3C2 / Sn-Bi-MOF composite photocatalyst can be used for photocatalytic reduction of CO2.
[0006] First, the present invention provides a g-C3N4 / Ti3C2 / Sn-Bi-MOF composite photocatalyst, wherein the g-C3N4 / Ti3C2 / Sn-Bi-MOF composite photocatalyst is a cluster structure, wherein the composite photocatalyst is first loaded with flaky Ti3C2 on the surface of a g-C3N4 sheet by mechanical stirring, and then loaded with irregular nanoparticle Sn-Bi-MOF on the surface of the g-C3N4 / Ti3C2 structure; the mass ratio of the g-C3N4, Sn-Bi-MOF and Ti3C2 is 1:1:0.125-0.5. Preferably, the mass ratio of the g-C3N4, Sn-Bi-MOF and Ti3C2 is 1:1:0.25-0.375.
[0007] Secondly, the present invention also provides a method for preparing the above-mentioned g-C3N4 / Ti3C2 / Sn-Bi-MOF composite photocatalyst, which specifically comprises the following steps:
[0008] (1) Preparation of g-C3N4: Urea is placed in a quartz crucible and heated for cracking.
[0009] The heating rate of urea thermal decomposition is 5°C / min and the duration is 2.5h.
[0010] (2) Preparation of Sn-Bi-MOF: SnCl2·2H2O and H2BDC were placed in a mixture of N,N-dimethylformamide and anhydrous ethanol and stirred, and then Bi(NO3)2·5H2O was added and stirred. Then, hexadecyltrimethylammonium bromide (CTAB) was added and stirred, and then a hydrothermal reaction was carried out. After the reaction was completed, the mixture was cooled, centrifuged, washed, and dried to obtain Sn-Bi-MOF.
[0011] The molar ratio of SnCl2·2H2O, H2BDC and Bi(NO3)2·5H2O is 2:1:1. The volume ratio of N,N-dimethylformamide to anhydrous ethanol is 4:1. The mass concentration of CTAB in the mixed solution is 1.25 mg / mL.
[0012] Furthermore, the conditions of the hydrothermal reaction are: reacting at 140-180° C. for 8-12 hours.
[0013] (3) Preparation of Ti3C2: LiF and HCl are mixed and then ultrasonically processed to obtain an etching solution. Ti3AlC2 is then immersed in the etching solution for etching. After the reaction is completed, the solution is cooled, centrifuged, washed, and dried to obtain Ti3C2.
[0014] The mass fraction of HCl in the etching solution is 36-38 wt %, and the concentration of LiF is 4 mol / L.
[0015] The molar concentration of HCl used for washing was 2 mol / L.
[0016] (4) Preparation of g-C3N4 / Ti3C2 / Sn-Bi-MOF composite photocatalyst: The g-C3N4, Ti3C2 and Sn-Bi-MOF obtained in steps (1), (2) and (3) are dissolved in a mixture of water and anhydrous ethanol respectively, and stirred until uniformly dispersed. Subsequently, the Ti3C2 suspension is slowly dropped into the g-C3N4 suspension, and then the Sn-Bi-MOF suspension is slowly dropped into the mixture of g-C3N4 and Ti3C2 and stirred evenly. The mixture is hydrothermally reacted under stirring until it becomes powder to obtain a g-C3N4 / Ti3C2 / Sn-Bi-MOF composite photocatalyst.
[0017] Furthermore, in step (4), the mass ratio of g-C3N4, Ti3C2 and Sn-Bi-MOF is 1:0.125 to 0.5:1; preferably, the mass ratio of g-C3N4, Ti3C2 and Sn-Bi-MOF is 1:0.125 to 0.375:1.
[0018] Furthermore, the hydrothermal reaction temperature in step (4) is 60°C.
[0019] Finally, the present invention also provides the use of the above-mentioned g-C3N4 / Ti3C2 / Sn-Bi-MOF composite photocatalyst in photocatalytic reduction of carbon dioxide.
[0020] Specifically, the application is: xenon lamp irradiation, adding deionized water, sacrificial agent (triethanolamine) and g-C3N4 / Ti3C2 / Sn-Bi-MOF composite photocatalyst into a photoreactor, and reacting under N2 gas atmosphere.
[0021] Furthermore, the dosage of deionized water, sacrificial agent and g-C3N4 / Ti3C2 / Sn-Bi-MOF composite photocatalyst is 80mL:20mL:50mg, that is, the concentration of the g-C3N4 / Ti3C2 / Sn-Bi-MOF composite photocatalyst in the reaction solution is 0.5g / L.
[0022] Compared with the prior art, the present invention has the following beneficial effects:
[0023] The present invention uses the porous structure of g-C3N4 as a carrier to improve the dispersibility of Sn-Bi-MOF and avoid the agglomeration of Sn-Bi-MOF. The g-C3N4 and Sn-Bi-MOF are in close contact to form a Z-type heterojunction, which can significantly inhibit the composite enhanced light absorption of electron-hole pairs. The introduction of Ti3C2 improves the transfer efficiency of photogenerated carriers. Therefore, the introduction of Ti3C2 in the heterojunction constructed by g-C3N4 and Sn-Bi-MOF can not only improve the charge separation effect of g-C3N4 but also increase its electron transfer rate. This study provides a new perspective for the construction of Z-type heterojunctions and Schottky junctions, and provides guidance for the efficient photocatalytic reduction of CO2.
[0024] The present invention realizes the purpose of photocatalytic reduction of CO2 using the cluster g-C3N4 / Ti3C2 / Sn-Bi-MOF as a composite photocatalyst. Under simulated sunlight irradiation, photocatalytic reduction of CO2 is achieved through the separation and transfer of photogenerated electron-hole pairs. The catalyst preparation method is simple and is a green and environmentally friendly energy conversion technology. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 XRD diagrams of Ti3ALC2 and Ti3C2.
[0026] Figure 2 XRD spectra of g-C3N4, Ti3C2, Sn-Bi-MOF, g-C3N4 / Sn-Bi-MOF and g-C3N4 / Ti3C2 / Sn-Bi-MOF composite photocatalysts.
[0027] Figure 3 This is the SEM spectrum of the g-C3N4 / Ti3C2 / Sn-Bi-MOF composite photocatalyst prepared in Example 1.
[0028] Figure 4 PL spectra of g-C3N4, Ti3C2, Sn-Bi-MOF, g-C3N4 / Sn-Bi-MOF and g-C3N4 / Ti3C2 / Sn-Bi-MOF composite photocatalysts.
[0029] Figure 5 This is the rate diagram of photocatalytic reduction of carbon dioxide.
[0030] Figure 6 This is the experimental rate diagram of the photocatalytic reduction of carbon dioxide cycle of g-C3N4 / Ti3C2 / Sn-Bi-MOF prepared in Example 1.
[0031] Figure 7 This is the XPS characterization diagram of the g-C3N4 / Ti3C2 / Sn-Bi-MOF photocatalyst prepared in Example 1. DETAILED DESCRIPTION
[0032] The present invention is further described below in conjunction with the accompanying drawings and specific embodiments, but the protection scope of the present invention is not limited thereto.
[0033] In the following examples, the photocatalytic activity was evaluated using the following steps: in a photoreactor, irradiated with a 300 W xenon lamp, 80 mL of deionized water and 20 mL of a sacrificial agent (triethanolamine) were added to the reactor, and then 0.05 g G-C3N4 / Ti3C2 / Sn-Bi-MOF composite photocatalytic material was added. After continuously blowing CO2 gas, the seal was evacuated and the xenon lamp light source was turned on, and samples were taken for analysis after 5 hours.
[0034] Example 1
[0035] Preparation of g-C3N4 / Ti3C2 / Sn-Bi-MOF composite photocatalytic materials:
[0036] (1) Preparation of g-C3N4:
[0037] 2 g of urea was heated to 520° C. at a rate of 5° C. / min for 2.5 h. The resulting powder was collected and ground for storage.
[0038] (2) Preparation of Sn-Bi-MOF:
[0039] 2.4mmol SnCl2·2H2O and 1.2mmol H2BDC were added to a mixture containing 36mL DFM and 9mL anhydrous ethanol. After stirring for half an hour, 1.2mmol Bi(NO3)2·5H2O was added and stirred for another half an hour. Then 50mg CTAB was added and stirred evenly. The solution was hydrothermally reacted at 170℃ for 8h. Cooled to room temperature, centrifuged, washed alternately with water and ethanol, and dried in an oven at 60℃ overnight to obtain Sn-Bi-MOF.
[0040] (3) Preparation of Ti3C2:
[0041] 2.07g LiF was mixed with 20mL HCl with a mass fraction of 36-38% to obtain a 4mol / L suspension. 0.5g Ti3AlC2 was soaked in the LiF suspension and stirred at 60°C for 48h. First, it was washed with deionized water, then diluted with 2mol / L hydrochloric acid for 3 times, washed with water again, and finally washed with ethanol twice until the pH was neutral. It was dried at 80°C for a day and night to obtain Ti3C2.
[0042] (4) Preparation of g-C3N4 / Ti3C2 / Sn-Bi-MOF composite photocatalyst:
[0043] 200 mg g-C3N4, 200 mg Sn-Bi-MOF, and 50 mg Ti3C2 were uniformly dispersed in 30 mL ethanol respectively, and then the Ti3C2 suspension was slowly added dropwise to the g-C3N4 suspension, and then the Sn-Bi-MOF suspension was slowly added dropwise to the mixed solution of g-C3N4 and Ti3C2, and then vigorously stirred at 60 °C until it became a powder to obtain a g-C3N4 / Ti3C2 / Sn-Bi-MOF composite photocatalyst (pCN / TC / Sn-Bi-MOF).
[0044] Example 2
[0045] In step (4) of this embodiment, the amount of Ti3C2 used is 25 mg, and the remaining steps are the same as in Example 1, to obtain a g-C3N4 / Ti3C2 / Sn-Bi-MOF-1 composite photocatalyst (pCN / TC / Sn-Bi-MOF-1).
[0046] Example 3
[0047] In step (4) of this embodiment, the amount of Ti3C2 used is 75 mg, and the remaining steps are the same as in Example 1 to obtain a g-C3N4 / Ti3C2 / Sn-Bi-MOF-2 composite photocatalyst (pCN / TC / Sn-Bi-MOF-2).
[0048] Example 4
[0049] In step (4) of this embodiment, the amount of Ti3C2 used is 100 mg, and the remaining steps are the same as in Example 1, to obtain a g-C3N4 / Ti3C2 / Sn-Bi-MOF-3 composite photocatalyst (pCN / TC / Sn-Bi-MOF-3).
[0050] Comparative Example 1
[0051] Preparation of g-C3N4 / Sn-Bi-MOF composite photocatalytic materials:
[0052] (1) Preparation of g-C3N4: Same as Example 1;
[0053] (2) Preparation of Sn-Bi-MOF: Same as Example 1;
[0054] (3) Preparation of g-C3N4 / Sn-Bi-MOF composite photocatalyst: 200 mg g-C3N4 and 200 mg Sn-Bi-MOF were dispersed evenly in 30 mL ethanol respectively, and then the Sn-Bi-MOF suspension was slowly added dropwise to the g-C3N4 mixed solution, followed by vigorous stirring at 60 °C until it became a powder to obtain a g-C3N4 / Sn-Bi-MOF composite photocatalyst (pCN / Sn-Bi-MOF).
[0055] Figure 1 XRD diagrams of Ti3AlC2 and Ti3C2; Figure 1 It can be seen that the (002) peak of Ti3AlC2 shifts to the left and the (104) peak representing Al atoms disappears, indicating that Ti3C2 was successfully prepared.
[0056] Figure 2 XRD spectra of g-C3N4, Ti3C2, Sn-Bi-MOF, g-C3N4 / Sn-Bi-MOF and g-C3N4 / Ti3C2 / Sn-Bi-MOF composite photocatalyst of Example 1; the figure clearly shows that the XRD spectrum of g-C3N4 / Ti3C2 / Sn-Bi-MOF contains the characteristic peaks of g-C3N4, Ti3C2 and Sn-Bi-MOF, which illustrates the successful synthesis of g-C3N4 / Ti3C2 / Sn-Bi-MOF composite photocatalyst.
[0057] Figure 3 This is the SEM image of the g-C3N4 / Ti3C2 / Sn-Bi-MOF composite photocatalyst; it can be seen from the figure that the g-C3N4 / Ti3C2 / Sn-Bi-MOF composite is successful, that is, it is obvious that the g-C3N4 loaded with clustered Sn-Bi-MOF wraps the layered Ti3C2.
[0058] Figure 4 PL spectra of g-C3N4, Ti3C2, Sn-Bi-MOF, g-C3N4 / Sn-Bi-MOF and g-C3N4 / Ti3C2 / Sn-Bi-MOF; it can be seen from the image that the PL intensity of the composite material is weak, which indicates that the electron-hole recombination rate is low.
[0059] Figure 5The photocatalytic reduction rate diagram of the prepared g-C3N4 / Sn-Bi-MOF, g-C3N4 / Ti3C2 / Sn-Bi-MOF-1, g-C3N4 / Ti3C2 / Sn-Bi-MOF, g-C3N4 / Ti3C2 / Sn-Bi-MOF-2, and g-C3N4 / Ti3C2 / Sn-Bi-MOF-3. It can be seen from the figure that g-C3N4 / Ti3C2 / Sn-Bi-MOF has better photocatalytic reduction performance.
[0060] Figure 6 This is a cycle experiment diagram of the g-C3N4 / Ti3C2 / Sn-Bi-MOF photocatalyst prepared in Example 1. It can be seen from the figure that after 4 cycle experiments, the CO yield of the catalyst only slightly decreased, indicating that pCN / TC / Sn-Bi-MOF has good photostability.
[0061] Figure 7 The overall spectrum and XPS characterization diagram of the g-C3N4 / Ti3C2 / Sn-Bi-MOF photocatalyst prepared in Example 1. The change in the binding energy of different orbital elements explains the flow direction of electrons in the reaction, proving the successful construction of the Z-type heterojunction.
[0062] In summary, the present invention prepares the g-C3N4 / Ti3C2 / Sn-Bi-MOF composite material by hydrothermal, etching and mechanical stirring method, the surface area is improved, the photocatalytic performance is also enhanced, and it has good cyclic reduction performance and good visible light response performance. Compared with other samples, the optimized g-C3N4 / Ti3C2 / Sn-Bi-MOF forms a Z-Scheme heterojunction under visible light irradiation. The maximum reduction yields of CO and CH4 are 2566μmol·h -1 ·g -1 and 34 μmol·h -1 ·g -1 , and the yield only slightly decreased after four cycles. This work provides an effective method for obtaining a stable photocatalytic CO2 reduction system.
[0063] The embodiments are preferred implementations of the present invention, but the present invention is not limited to the above-mentioned implementations. Any obvious improvements, substitutions or modifications that can be made by those skilled in the art without departing from the essential content of the present invention belong to the protection scope of the present invention.
Claims
1. A g-C3N4 / Ti3C2 / Sn-Bi-MOF composite photocatalyst, characterized in that: The g-C3N4 / Ti3C2 / Sn-Bi-MOF composite photocatalyst has a cluster structure. The g-C3N4 / Ti3C2 / Sn-Bi-MOF composite photocatalyst is prepared by first growing flaky Ti3C2 on the surface of flaky g-C3N4 and then growing irregular nanoparticle Sn-Bi-MOF on the surface of flaky Ti3C2 by mechanical stirring. The mass ratio of g-C3N4, Sn-Bi-MOF and Ti3C2 is 1:1:0.125-0.
5.
2. A method for preparing the g-C3N4 / Ti3C2 / Sn-Bi-MOF composite photocatalyst as claimed in claim 1, characterized in that: The specific steps include: (1) Preparation of g-C3N4: Urea is placed in a quartz crucible for heating and cracking; (2) Preparation of Sn-Bi-MOF: SnCl2·2H2O and H2BDC are placed in a mixture of N,N-dimethylformamide and anhydrous ethanol and stirred, Bi(NO3)2·5H2O is added and stirred evenly, and then hexadecyltrimethylammonium bromide is added and stirred evenly to obtain a mixed solution, and the mixed solution is subjected to a hydrothermal reaction. After the reaction is completed, the solution is cooled, centrifuged, washed, and dried to obtain Sn-Bi-MOF; wherein the molar ratio of SnCl2·2H2O, H2BDC, and Bi(NO3)2·5H2O is 2:1:1; and the volume ratio of N,N-dimethylformamide to anhydrous ethanol is 4:1; (3) Preparation of Ti3C2: Ti3AlC2 is immersed in an etching solution mixed with LiF and HCl for etching. After the reaction is completed, the mixture is cooled, centrifuged, washed, and dried to obtain Ti3C2; (4) Preparation of g-C3N4 / Ti3C2 / Sn-Bi-MOF composite photocatalyst: The g-C3N4 obtained in step (1) is uniformly dispersed in a mixture of water and anhydrous ethanol to obtain a g-C3N4 suspension; the Ti3C2 obtained in step (2) is uniformly dispersed in a mixture of water and anhydrous ethanol to obtain a Ti3C2 suspension; the Sn-Bi-MOF obtained in step (3) is uniformly dispersed in a mixture of water and anhydrous ethanol to obtain a Sn-Bi-MOF suspension; then the Ti3C2 suspension is slowly dropped into the g-C3N4 suspension, and then the Sn-Bi-MOF suspension is slowly dropped into the mixture of g-C3N4 and Ti3C2 and stirred evenly, and a hydrothermal reaction is carried out under stirring until it becomes a powder to obtain a g-C3N4 / Ti3C2 / Sn-Bi-MOF composite photocatalyst.
3. The method for preparing the g-C3N4 / Ti3C2 / Sn-Bi-MOF composite photocatalyst according to claim 2, characterized in that: In step (2), the mass concentration of hexadecyltrimethylammonium bromide in the mixed solution is 1.25 mg / mL.
4. The method for preparing the g-C3N4 / Ti3C2 / Sn-Bi-MOF composite photocatalyst according to claim 2, characterized in that: In step (2), the conditions of the hydrothermal reaction are: reacting at 140-180° C. for 8-12 hours.
5. The method for preparing the g-C3N4 / Ti3C2 / Sn-Bi-MOF composite photocatalyst according to claim 2, characterized in that: In step (3), the mixed etching solution of LiF and HCl is obtained by uniformly mixing LiF and HCl with a mass fraction of 36-38 wt %, and the molar concentration of LiF is 4 mol / L.
6. The method for preparing the g-C3N4 / Ti3C2 / Sn-Bi-MOF composite photocatalyst according to claim 2, characterized in that: The mass concentration of the g-C3N4 suspension is 6-7 mg / ml; the mass concentration of the Ti3C2 suspension is 0.8-3.5 mg / ml; and the mass concentration of the Sn-Bi-MOF suspension is 6-7 mg / ml.
7. The method for preparing the g-C3N4 / Ti3C2 / Sn-Bi-MOF composite photocatalyst according to claim 2, characterized in that: In step (4), the hydrothermal reaction temperature is 60°C.
8. An application of the g-C3N4 / Ti3C2 / Sn-Bi-MOF composite photocatalyst as claimed in claim 1, characterized in that: Application of the g-C3N4 / Ti3C2 / Sn-Bi-MOF composite photocatalyst in photocatalytic reduction of carbon dioxide.
9. The use of the g-C3N4 / Ti3C2 / Sn-Bi-MOF composite photocatalyst according to claim 8, characterized in that: The method comprises the following steps: irradiating with a xenon lamp, adding deionized water, a sacrificial agent and a g-C3N4 / Ti3C2 / Sn-Bi-MOF composite photocatalyst into a photoreactor, and reacting in a N2 gas atmosphere.
10. The use of the g-C3N4 / Ti3C2 / Sn-Bi-MOF composite photocatalyst according to claim 9, characterized in that: The dosage of the g-C3N4 / Ti3C2 / Sn-Bi-MOF composite photocatalyst is 0.5 g / L.
Citation Information
Patent Citations
Carbon nitride nanosheet-loaded titanium carbide quantum dot composite material and preparation method and application thereof
CN110013869A
Preparation method of two-dimensional titanium carbide / two-dimensional graphite phase carbon nitride nanosheet heterojunction and application of heterojunction in photocatalytic reduction of CO2
CN111215115A